Análise do processo de gestão da informação e suas possíveis contribuições na implementação da lei geral de proteção de dados pessoais no Tribunal Regional da Paraíba - Souza, Marilídia de Lourdes Silva de (2022)
The present research seeks to analyze the Information Management process and its contributions to the implementation of the General Perssonal Data Protection Law in the Regional Electoral Court of Paraíba. The methodological procedures of the research integrate the qualitative approach, characterized as an exploratory, applied and descriptive research, in addition to the use of bibliographic, documentary and field research for data collection. As for the research instruments, semi-structured interviews and online focus groups will be used for all categories of audiences at the Court. Regarding data analysis, a content analysis method will be used, based on Bardin's categorization and classification technique. These are the categories: information needs; information acquisition; organization and storage of information; development of information products and services; distribution of information and use of information, according to the model proposed by Choo (2003). Finally, a comparison will be made between Information Management and the General Personal Data Protection Law, to assess the extent to which the phases of the management process have direct or indirect implications for the implementation of said law, in that court.